The youngest rostroconch mollusc from North America, Minycardita capitanensis n. sp. - Vendrasco, Michael J.; Hoare, Richard D.; Bell, Jr, Gorden L. (Zootaxa, 2010)
Rostroconchs are an extinct class of mollusc that lived worldwide through most or all of the Paleozoic Era (Runnegar 1978). They were most diverse in the early Paleozoic (Pojeta 1985), perhaps due to a lower rate of evolution in the rostroconch clade that survived the end-Ordovician mass extinction event (Wagner 1997). Rostroconchs have a univalved larval shell and a pseudo-bivalved adult shell. Their ecology appears to have ranged from infaunal to rarely epifaunal, and from deposit to suspension feeding (Pojeta et al. 1972, Pojeta & Runnegar 1976, Runnegar 1978, Pojeta 1987). A single but well-preserved, essentially complete rostroconch specimen was recovered from the region surrounded by the famous Capitan Reef of the Permian of West Texas (Newell et al. 1953). In particular, the specimen is from the upper scaphopod bed of the Reef Trail Member of the Bell Canyon Formation exposed in the Guadalupe Mountains National Park (Rigby & Bell 2005: fig. 2). The fusulinid biostratigraphic zonal indicator Paraboultonia splendens Skinner & Wilde, 1954 occurs both below the upper scaphopod bed and above it, indicating that this horizon was deposited during the latest Guadalupian (late middle Permian) (Rigby & Bell 2006), and thus is the youngest known deposit in North America to contain a rostroconch. Most known Permian rostroconchs have been recovered from rocks in North America, and only one occurrence stands out as clearly younger than this one: Pseudoconocardium Zavodowsky, 1960 from the Late Permian of Siberia, a large rostroconch that differs significantly in shape and ornamentation from rostroconchs of the late Paleozoic in North America (Hoare et al. 2002). Permian rostroconchs are rare, having been described from only sixteen localities worldwide (listed in Hoare & Plas 2003). In contrast, rostroconchs were relatively abundant during the preceding Pennsylvanian (Hoare et al. 2002). Thus the occurrence described herein represents the youngest known record of the North American rostroconch lineages, and is one of the last snapshots of a major molluscan clade.